Molecular phylogeny, biogeography, and conservation status of the Texas-endemic freshwater mussel Lampsilis bracteata (Bivalvia, Unionidae) - Porto-Hannes, Isabel; Burlakova, Lyubov E.; Karatayev, Alexander Y.; Lasker, Howard R. (Zootaxa, 2019)
Lampsilis bracteata (Gould), the Texas Fatmucket, is a regional endemic species in the central Texas biogeographic province which is a candidate to be listed as threatened or endangered under the Endangered Species Act of 1973. Lampsilis bracteata is morphologically similar to the common species L. hydiana (Lea). Here, we examine the molecular taxonomic identification of L. bracteata, and compare its historical range with its current geographic distribution. Tests of genetic affinities based on two mitochondrial genes typically used for DNA barcoding (cytochrome oxidase subunit 1, COI and NADH dehydrogenase subunit 1, ND1) support recognition of L. bracteata as a full species. An unexpected spin-off result was that ND1 sequences of L. satura (Lea), a threatened species in Texas, formed a highly supported cluster within putative L. cardium Rafinesque. As an endemic species, the distribution of L. bracteata has been historically restricted; however, poor land and water management practices have further reduced its distribution from eighteen to just eight streams in the Colorado River drainage and to one stream in the Guadalupe River drainage. For L. bracteata, as for many other imperiled freshwater mussel species, effective conservation measures rely on correct species identification, definition of its geographic range and assessment of its changes in the recent past.